Validation of the family Bathyporeiidae (Crustacea, Amphipoda) - D'acoz, Cedric D'udekem (Zootaxa, 2011)
The family Bathyporeiidae was introduced without description, and later on, when its first proper description appeared, was not considered as new. Therefore, it cannot be currently considered as a valid family. These procedural irregularities are corrected herein, and the the family is described de novo, with Bathyporeia as its type genus.